A Comprehensive review on hydroelectric cell: A green energy source for sustainable development. Issue 1 (May 2021) - Singh, R. K.; Manash, A.; Kumar, S.S.; Satyapal, H. K.; Kumar, G.; Shankar, U.
Abstract: A thorough analysis of the hydroelectric cell, in which electric charges are produced by redox reaction, was attempted. As electrodes, zinc & silver are used, with zinc serving as an anode & silver acting as a cathode. Hydroelectric Cell is a capable, environmentally friendly energy generation system that provides several benefits to humans. HEC is a straightforward, low-cost, & novel technique. The recently developed HEC is proving to be superior alternative to environmentally friendly electrical energy products. For the HEC fabrication, various ferrite nanomaterials such as magnesium, nickel, and others were used. The significance of the recent study is that it focuses on green energy generation, which is an alternative source in today's energy demand. In addition, hydroelectric cell output is predictable and consistent, and it has the capability to substitute conventional methods of generating renewable energy in terms of cost & security.